An infectious diseases perspective on the microbiome and allogeneic stem cell transplant. Issue 6 (December 2020) - Smibert, Olivia C.; Trubiano, Jason A.; Slavin, Monica A.; Kwong, Jason C.
Abstract : Purpose of review: The gut microbiome presents a novel source of diagnostic and therapeutic potential to modify post allogeneic stem cell transplant complications. There is an explosion of interest in microbiome research, mostly in the form of single-centre prospective time-series cohorts utilizing a variety of sampling frequencies and metagenomic technologies to sequence the microbiome. The purpose of this review is to summarize important recent publications and contextualize them within what has already been described in this rapidly growing field. Recent finding: Results from observational human cohort and animal transplant models add to the growing body of evidence that the microbiome modulates the immunopathogenesis of posttransplant complications. This is particularly the case for recipients of grafts replete with T cells where the evidence that acute graft-versus-host disease is mediated by anaerobic commensal-associated short-chain fatty acids, which interact with mucosa-associated (CD4 + FOXP3 + ) T-regulatory cells. Summary: Future human research into the role of the microbiome in allogeneic stem transplant should incorporate rigorous and considered experimental design in addition to next-generation sequencing technology to better portray microbiome functional potential and active gene expression. In combination with host immune phenotyping, which would facilitate a robust understanding of the host--microbiome interaction that is required before meaningful translation into clinical diagnostics and therapeutics can be expected.